(untitled) (Ukrainian Journal of Ophthalmology, 2026)
Background: A great deal of evidence has been accumulated over the last decade indicating that a failure of immunologic control mechanisms plays an important role in the tumor initiation and growth. Our experience argues that a systemic approach to the treatment of cancer will allow not only the enhancement of capabilities of the organ-saving treatment, but also the improvement of prognosis for survival time. Purpose: To investigate the immunomodulating effect of adjuvant interferon inducer, tilorone, in patients receiving the combined photocoagulation/ strontium-90 brachytherapy treatment for uveal melanoma. Materials and Methods: This prospective study involved 83 uveal melanoma patients of the Filatov institute oncology department. They were divided into two groups comprising 43 patients who received the combined treatmentwith adjuvant tilorone therapy, and 40 patients whose disease was managed by the combined treatment alone, respectively. The immunological status was determined at the baseline, and at 3-, 6-, and 9-month time points of the study. Results: In both groups, the baseline immunological features were decreased CD8 (suppressor T cells/ cytotoxic T cells) percentage, increased CD4/CD8 ratio, and subnormal CD16 (natural killer cells) percentage, whereas the baseline humoral immunity features were increased IgA levels with respect to healthy controls. When used as an adjuvant to the combined treatment for uveal melanoma, tilorone offers benefit beyond the combined treatment alone with respect to normalization of the immunological status of the patients (including normalization of suppressor T cells/ cytotoxic T cells (CD8) percentage, NK cells (CD16) percentage, and CD4/CD8 ratio). Additionally, normalization of IgA levels is observed. Conclusion: Tilorone can be integrated into a complex modality approach for uveal melanoma treatment as an immune correction agent with the anti-tumor resistance-enhancing capacity.